Constructing Synergistic Zn‐N4 and Fe‐N4O Dual‐Sites from the COF@MOF Derived Hollow Carbon for Oxygen Reduction Reaction. Issue 4 (7th April 2022) - Miao, Qiyang; Yang, Shuai; Xu, Qing; Liu, Minghao; Wu, Ping; Liu, Guojuan; Yu, Chengbin; Jiang, Zheng; Sun, Yuhan; Zeng, Gaofeng
Abstract : Synergistic Dual‐Sites for Oxygen Reduction Reaction In article number 2100225, Qing Xu, Chengbin Yu, Gaofeng Zeng, and co‐workers constructed synergistic dual‐sites for catalyzing oxygen reduction reaction from a core‐shell hybrid of a covalent organic framework (COF) and a metal organic framework (MOF). The synergistic effect between the Fe and Zn sites made the catalysts with high activity and selectivity. This provides a new insight into developing electrocatalysis from COFs and MOFs.